Development of MS ISO/IEC 17025 quality system (general requirements for the competence of testing and calibration laboratories) for FKM laboratory - Hue, Wei Jy (2009)
This report illustrates the development of quality documents of MS ISO/IEC 17025:2005 at FKM Laboratory of Universiti Malaysia Pahang (UMP). This report consists of five chapters which are Introduction, Literature Review, and Methodology, Results and Discussions, and Conclusion. The objectives of this project are to identify the clauses of MS ISO/IEC 17025:2005 and develop the quality documents according to the standard for FKM Laboratory. MS ISO/IEC 17025:2005 mainly divides into two main clauses which are management requirements and technical requirements. The management requirements are similar to the requirements of ISO 9001. To understand more on the project, the requirements of ISO 9001 were being studied. After referred to several books, the requirements of ISO 9001 are actually borrow from the principles of total quality management (TQM). Therefore, the principles of TQM and the studies that relate to quality were also being studied. In order to achieve the objectives of the project, it is important to understand the clauses of MS ISO/IEC 17025:2005. Therefore, the clauses of the standard were being studied. After that, the quality documents such as quality manual and system procedure were developed for FKM Laboratory according to MS ISO/IEC 17025:2005. To have a clearer mind in developing the quality documents, a course on MS ISO/IEC 17025:2005 was attended to understand more on the clauses as well as the development of quality manual. By the way, one of the accredited laboratories had been chosen to visit. It was also to make sure the quality manual and procedure that had been develop is in the right path. Thus, the laboratory visit is necessary. The documents that had been developed in this project are quality manual, system procedure, and forms and records. Quality manual had been developed for clause 4.1 to clause 4.8. System procedure also had been developed for clause 4.3 to clause 4.8. The system procedure for clause 4.1 and clause 4.2 were not developed since all the requirements had already stated in quality manual. For clause 4.5 which is subcontracting tests and calibrations, is not applicable since FKM Laboratory is more focus on the activities of research and development. All the documents will be proposed to FKM Laboratory management to the accreditation of MS ISO/IEC 17025:2005. In conclusion, the objectives had been achieved where all the related documents had been developed after identify the clauses.